Is Medicolegal Autopsy necessary in Diagnosed Natural Deaths? - Sarkar , R; Dutta , SS; Banerjee , M; Bari , A; Nadeem, S (Journal of Indian Academy of Forensic Medicine, 2024)
Medicolegal autopsies are performed in unnatural, sudden and suspicious deaths to find out mostly the cause, manner and mode of death. With the annual autopsy load of 3718 in the year 2022 at our centre, 524 cases consisted of diagnosed natural deaths where the cause of death was known to the physician yet they were sent for medicolegal autopsy as initially it was registered as a medicolegal case. Estimation of magnitude of natural deaths coming for medicolegal autopsy with an aim to find out whether the autopsy findings provided any extra merit over the diagnosed clinical findings including the cause of death that is, the relevance of medicolegal autopsy in natural deaths. It is a retrospective, descriptive and cross-sectional study which took 524 cases of diagnosed natural deaths coming for medicolegal autopsy at our centre in the year 2022 amongst which unidentified cases, unnatural death cases, cases which were brought dead to the hospital, sudden deaths, deaths with suspicion of foul play, cases where no clear history of the disease were available to us and cases where medical records of the deceased could not be arranged were excluded. Out of all such diagnosed natural death cases, majority of the cases (255 cases) (48.6%) died due to sepsis and the least common cause being diseased condition of the heart which constituted (56 cases) (10.6%) amongst such diagnosed natural deaths. On medicolegal autopsy, there were no extra appreciable findings which could justify the physician’s decision of sending the deceased for medicolegal autopsy.